Bio‐inspired Catalyst‐Modified Photocathode for Bias‐Free Photoelectrochemical NADH Regeneration - Ziqi Zhao; Yizhou Wu; Chang Liu; Yingzheng Li; Chen Gong; Hongxia Ning; Peili Zhang; Fei Li; Licheng Sun; Fusheng Li (Advanced Science)
Abstract Cofactors such as nicotinamide adenine dinucleotide (NADH) and its phosphorylated form (NADPH) play a crucial role in natural enzyme‐catalyzed reactions for the synthesis of chemicals. However, the stoichiometric supply of NADH for artificial synthetic processes is uneconomical. Here, inspired by the process of cofactor NADPH regeneration in photosystem I (PSI), catalyst‐modified photocathodes are constructed on the surface of polythiophene‐based semiconductors (PTTH) via self‐assembly for photoelectrochemical catalytic NADH regeneration. With the assistance of viologen (vi2+) electron transfer mediators (similar function as Ferredoxin in PSI) linked to the [Rh(Cp*)(bpy)] catalyst, the Rh‐vi2+@PTTH photocathode exhibits higher photocurrent density (−665 µA cm−2) with a high apparent turnover frequency (TOF, 168.4 h−1) under a relatively positive potential (0.0 V vs RHE). In addition, through holistic functional mimics of the photosystem, a tandem photoelectrochemical cell is constructed by assembling a CoPi@BiVO4 photoanode (artificial photosystem II, PSII) with the Rh‐vi2+@PTTH photocathode. This system achieves a production rate of 42.5 µm h−1 cm−2 and a TOF of 179.3 h−1 without an externally applied bias for NADH regeneration. The photo‐generated NADH is directly employed to assist glutamate dehydrogenase (GDH) in the catalytic conversion of α‐ketoglutarate to L‐glutamate. This study presents a novel strategic approach for constructing bias‐free photoelectrochemical NADH regeneration systems.